Desenvolvimento de competências das pessoas que atuam em projetos - Abbud, Ricardo Hares (2021)
The need to generate more and more competitive products with greater speed makes people in projects, who generate these products, pressured by lower deadlines, costs and suffering from restrictions of both material and human resources. In this context, there was a need for people who work in project management to develop and demonstrate technical, social-emotional and managerial skills, in order to meet the competitive environment with improved performance and maintenance of quality in meeting the requirements. These skills can be developed in an imbalance between technical and social-emotional, as well as lack of support from the organization in directing and prioritizing the development of skills. Based on this information, this dissertation aimed to describe the skills development practices of people who work on projects. This research adopted an exploratory perspective based on a systematic literature review (SLR), followed by qualitative empirical research based on in-depth interviews, which allowed to investigate the theme of the development of people who work on projects in greater depth. In the first phase, academic articles were analyzed and categorized, allowing the main categories of analysis to be established. In the second phase, 21 in-depth interviews were conducted with people responsible for project management to understand the nature of people development in projects. As for the process of analyzing the interviews, the Grounded Theory technique with coding cycles was adopted. Each category resulting from the field research data (data driven) was compared with the categories created in the Systematic Literature Review (theory driven), as a means of identifying practices and prescriptions for the development of people who work on projects. Afterwards, the results of the two phases of the research were mapped and compared, showing similarities and divergences. The results obtained from the mapped and compared items, showed convergence of interests in the way of developing competences in a formal way, through knowledge transfer and the type of competence development obtained in the project (learning by doing). However, it showed divergent directions when dealing with informal and problem-based development. This research contributes to practice by generating a prescription for the competence development process, as well as for theory, by identifying new research opportunities such as the effect of the company-university partnership and the project management approach in the development of competences in projects. In this way, the research collaborates by shed light on the need to address the development of socio-emotional skills of people who play roles in project management, future managers and squads, considering different methodological approaches from studies at the university level, as well as throughout the professional cycle. It also collaborates by pointing out in its field research the importance of Corporate Universities and the high incidence of informal competence development.